Green Investment and Renewable Energy Mix: Evidence from Indonesia - Nabella, Septa Diana; Rivaldo, Yandra; Endri, Endri; Wahyudi, Sely Megawati; Tanjung, Putri Renalita Sutra (International Journal of Energy Economics and Policy, 2025)
This research aims to prove the moderating role of green investment in population growth, economic growth, and foreign investment in the renewable energy mix in Indonesia. Data from the Indonesian Central Statistics Agency, World Development Indicators, Indonesian Investment Coordinating Board, and companies in the LQ45 Index with data from 2017 to 2023. The data was analyzed using a quantitative time series data regression analysis model using the Eviews 10 program. Research findings show that economic and population growth has a positive and significant effect through the moderation of green investment in Indonesian LQ45-indexed companies on the renewable energy mix. Foreign investment does not significantly impact the renewable energy mix by moderating green investment in Indonesian LQ45-indexed companies. This research contribution provides insight into how certain economic factors influence renewable energy and the role of green investments in changing the dynamics of indexed corporate relationships in Indonesian financial markets.